2011
DOI: 10.1128/iai.01249-10
|View full text |Cite
|
Sign up to set email alerts
|

Blastomyces dermatitidis Yeast Cells Inhibit Nitric Oxide Production by Alveolar Macrophage Inducible Nitric Oxide Synthase

Abstract: The ability of pathogens to evade host antimicrobial mechanisms is crucial to their virulence. The dimorphic fungal pathogen Blastomyces dermatitidis can infect immunocompetent patients, producing a primary pulmonary infection that can later disseminate to other organs. B. dermatitidis possesses a remarkable ability to resist killing by alveolar macrophages. To date, no mechanism to explain this resistance has been described. Here, we focus on macrophage production of the toxic molecule nitric oxide as a poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 37 publications
(34 reference statements)
0
28
0
Order By: Relevance
“…While our flow cytometric analysis was not sensitive enough to reliably detect leukocyte interactions with <10 4 spores, others have reported that as few as 70 spores are sufficient to cause disease and death in mice (29). While the inoculum of spores that causes disease in humans is unknown, our findings demonstrate that at low inocula most of the infectious spores enter alveolar macrophages, a niche in which they undergo morphogenesis to initiate infection and suppress innate host defense such as NO and TNF-α production (30, 31). …”
Section: Discussionmentioning
confidence: 87%
“…While our flow cytometric analysis was not sensitive enough to reliably detect leukocyte interactions with <10 4 spores, others have reported that as few as 70 spores are sufficient to cause disease and death in mice (29). While the inoculum of spores that causes disease in humans is unknown, our findings demonstrate that at low inocula most of the infectious spores enter alveolar macrophages, a niche in which they undergo morphogenesis to initiate infection and suppress innate host defense such as NO and TNF-α production (30, 31). …”
Section: Discussionmentioning
confidence: 87%
“…IFN-γ activated macrophages have been shown to have fungicidal activity against Histoplasma capsulatum (84-86) while presence of IL-4 and IL-10 results in inhibition of apoptosis and increase in disease severity (87). M1 activated macrophages have also been associated with antifungal effects against Aspergillus fumigatus (88), Blastomyces dermatitidis (89-91), and Paracoccidioides brasiliensis (90, 92, 93). Therefore, the development of therapeutics that induce M1 macrophage activation via an IFN-γ/STAT1 mechanism may provide protection against a myriad of microbial pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Conidia which escape the initial phagocytic response rapidly convert to a yeast form that is more resistant to phagocytosis and killing. In in vitro studies, B. dermatitidis yeast evades macrophage defenses [28] and suppresses nitric oxide production by inhibition of inducible nitric oxide synthase [29]. Several virulence factors have been associated with the pathogenicity of B. dermatitidis.…”
Section: Pathogenesis and Immunologymentioning
confidence: 99%